Impact network analysis and the ina r package: Decision support for regional management interventions. Issue 9 (8th July 2021) - Garrett, Karen A.
Abstract: The success of intervention projects for species management depends on both the effectiveness of management technologies and the geographical landscape of management adoption. Impact network analysis (INA) is a new framework for evaluating the likely level of success of regional species management before, during and after projects, for project implementers, policymakers and funders. INA evaluates the effects of management performance in a multilayer network analysis. The socioeconomic network represents manager communication about technologies and influence about technology adoption decisions in an agent‐based model. The linked biophysical network represents species dispersal, resulting in regional success or failure of species management. The specific objectives of this paper are to (a) introduce the INA framework and ina r package; (b) illustrate the identification of key nodes for smart surveillance strategies; (c) illustrate the application of the INA framework for evaluating the likely degree of success of a project in intervention ecology, before, during and after an intervention; and (d) illustrate the use of INA for evaluating adaptation strategies under global change scenarios with pulse and press stressors, introducing 'adaptation functions' to evaluate the management response required for sustainability and resilience. Examples of use of the ina package show key outcomes of analyses: identifying the limiting factors for effective regional management, pointing out when systems may be non‐responsive to the system components that are readily changed through management decisions, and identifying the additional adaptations that may be necessary for intervention success. The broader goals for the development of impact network analysis and the ina package are to provide a common framework that integrates across intervention ecology, to enhance opportunities for lessons learned across systems and scientific disciplines, to support the development of a community of practice, and to create a general platform to operationalize analysis of sustainability, resilience and economic viability in intervention ecology applications. Resumen: El éxito de proyectos de intervención depende de la eficacia en la adopción de tecnologías de manejo ambiental y agrícola. El análisis de impacto de redes (INA, por sus siglas en inglés) es un sistema de evaluación de la probabilidad del éxito regional sobre el manejo de especies – antes, durante, y después de un proyecto de intervención – para los encargados de implementar los proyectos, políticos, donadores e inversionistas. INA evalúa los efectos y el rendimiento del manejo utilizando un análisis de redes multicapas. La red socioeconómica represente la comunicación entre gerentes y la influencia que tienen sobre la toma de decisiones para la implementación, en un modelo basado en agentes. La red biofísica represente la dispersión de especies, resultando en el éxito o el fracaso del manejo de éstas. Los objetivos de este manuscrito son (1) introducir el sistema INA y el programa INA en R, (2) ilustrar la identificación de los nodos claves para su monitoreo inteligente, (3) ilustrar la aplicación del sistema INA para evaluar el grado probable de éxito de un proyecto de intervención ecológica– antes, durante, y después de un proyecto, y (4) ilustrar el uso de INA para evaluar las estrategias de adopción en diferentes escenarios de cambio global con estresores intermitentes y continuos, con una serie de funciones que se adaptan para poder evaluar los niveles de manejo requeridos de sustentabilidad y resiliencia. Los ejemplos del uso del programa INA muestran los resultados claves de los análisis: identifica los factores limitantes por el manejo regional, muestra cuando los sistemas tal vez no respondan a algunos componentes que pueden ser fácilmente cambiados por decisiones de manejo, así como también identifica qué ajustes adicionales pueden ser necesarios para el éxito de las intervenciones. Los principales objetivos del desarrollo del análisis de impacto de redes y del programa INA, son proveen de un sistema general que integra los conceptos de intervenciones ecológicas y potencian la oportunidad de aprender de otros sistemas y disciplinas científicas, favoreciendo el desarrollo de prácticas de grupos con intereses en común, y la creación de un sistema general operacional para el análisis de sustentabilidad, resiliencia, y viabilidad económica aplicadas a la ecología de intervención.